Jewish, Christian and Muslim theological perspectives about xenotransplantation. (24th April 2018) - Paris, Wayne; Seidler, Rabbi Jerry H.; FitzGerald, Kevin; Padela, Aasim I.; Cozzi, Emanuele; Cooper, David K. C.
Abstract: Background: This paper is based on a theological symposium presented at the International Xenotransplantation Association's 14th Congress held in Baltimore, MD, September, 2017. Methods: The information explores the Jewish, Christian and Muslim theological perceptions and perspectives about cross‐species (ie pig‐to‐human) organ transplantation, the genetic alterations required in the organ‐source pig, and their potential to influence individual acceptance of the procedure. Results/Conclusions: This work should not be considered as the ultimate word about individual theological views, but rather as part of an ongoing conversation that will hopefully lead to wider consideration and exploration of these issues as xenotransplantation science advances towards clinical trials.